قياس الأداء المتوازن و دوره في زيادة فعالية أداء المنظمات (دراسة مقارنة تحليلية لمشفى الأسد الجامعي و المشفى الوطني في مدينة اللاذقية) - تركمان حنان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت الدراسة إلى توضيح مفهوم بطاقة الأداء المتوازن و أسباب ظهورها و المحاور الرئيسية التي تبنى عليها و مزايا و فوائد استخدامها, إضافة إلى خطوات بناء البطاقة و استخدامها كأداة لقياس الأداء , و ميزات التطبيق الناجح لبطاقات القياس المتوازن , و مشكلات استخدامها. يشتمل مجتمع البحث على مشفى الأسد الجامعي و المشفى الوطني في مدينة اللاذقية من خلال دراسة مقارنة تحليلية و الاعتماد على الإستبانة لجمع البيانات حيث تم توزيع80 استبيان تم الحصول من خلالها على إجابات أفراد العينة عن الموضوع محل الدراسة و قد توصل البحث إلى عدة نتائج من أهمها أن هناك علاقة بين مستوى الأداء و نوع الأداة المستخدمة في قياس الأداء , و هناك اثر إيجابي لاستخدام بطاقة الأداء المتوازن كمقياس شامل للأداء . لذلك أوصت الدراسة بضرورة استخدام بطاقة قياس الأداء المتوازن في المشافي محل الدراسة عند وضع الإستراتيجيات العامة لما لها من فائدة كبيرة في تحديد مستوى الأداء الفعلي. This study aims to explain the concept of Balanced Scorecard and the reasons for its appearance, also the main themes that originates from it, and the advantages and benefits from its usage. In addition to that the work aims to explain the required steps to build the card and use it as a tool to measure the performance and the benefits of optimal implementing for Balanced Scorecard and the problems of its usage. Research community includes Al Assad University Hospital and the National Hospital in Latakia based on comparative and analytical study for a questionnaire to collect the data. Eighty questionnaires have been distributed to obtain responses from the available samples about the subject of the study. Obtained results show that there is a relationship between the performance level and type of the tool used to measure the performance. Moreover, there is a positive impact for the use of the Balanced Scorecard as a scale of overall performance. The study strongly recommended to use balanced scorecards in the hospitals (included in the study) when planning their general strategies, due to its significant advantages in determining the actual performance.